Evaluation of the efficiency between two biofilter systems for the treatment of domestic wastewater in the locality of Carapongo, Lurigancho-Chosica - Quispe Pulido, Andrea (2019)
The objective of this research was to evaluate the efficiency between two biofilter pilot systems for the treatment of wastewater, by analyzing the physical - chemical and microbiological parameters, in order to provide a contribution in the treatment and reuse of wastewater. for irrigation purposes of crops and to mitigate the contamination in the irrigation canals and as a consequence in the Rimac river for the benefit of the inhabitants and the environment. To do this, an experimental design was used, two biofilters of similar characteristics were implemented, the first biofilter system (SB1) conformed by a roughing channel, septic tank, subsurface vertical flow wetland (HSSFV) and surface wetland (HS), and the second biofilter system (SB2) consisting of a roughing channel, septic tank, vermicomeller and surface wetland; using the species Cyperus papyrus, Alocasia macrorrhiza and Eichhornia crassipes in SB1, Eisenia foetida and Eichhornia crassipes in SB2. The results obtained from the parameters Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD5), nitrate (NO-3), nitrite (NO-2), phosphates (PO4-3) and Thermotolerant Coliforms (TC) were recorded during Two months, reaching the following conclusions, SB1 was more efficient in the removal of SST, BOD5 and CT with values of 95.71%, 91.55% and 99.87%, respectively. Meanwhile, SB2 presented values of 90.33%, 91.23% and 97.28%, respectively. On the other hand, SB2 showed a greater removal of PO4-3 with a value of 94.5% compared to 92.23% in SB1.